ADP Platelet Hyperreactivity Predicts Cardiovascular Disease in the FHS (Framingham Heart Study). Issue 5 (3rd March 2018) - Puurunen, Marja K.; Hwang, Shih‐Jen; Larson, Martin G.; Vasan, Ramachandran S.; O'Donnell, Christopher J.; Tofler, Geoffrey; Johnson, Andrew D.
Abstract : Background: Platelet function is associated with adverse events in patients with cardiovascular disease (CVD). Methods and Results: We examined associations of baseline platelet function with incident CVD events in the community‐based FHS (Framingham Heart Study). Participants free of prevalent CVD and without recent aspirin treatment with available data in the Framingham Offspring cohort (1991–1995) and Omni cohort (1994–1998) were included. Platelet function was measured with light transmission aggregometry using collagen (1.9 μg/mL), ADP (0.05–15 μmol/L), and epinephrine (0.01–15 μmol/L). We used proportional hazards models to analyze incident outcomes (myocardial infarction/stroke, CVD, and CVD mortality) with respect to platelet measures. The study sample included 2831 participants (average age, 54.3 years; 57% women). During follow‐up (median, 20.4 years), we observed 191 composite incident myocardial infarction or stroke events, 432 incident CVD cases, and 117 CVD deaths. Hyperreactivity to ADP and platelet aggregation at ADP concentration of 1.0 μmol/L were significantly associated with incident myocardial infarction/stroke in a multivariable model (hazard ratio, 1.68 [95% confidence interval, 1.13–2.50] [ P =0.011] for hyperreactivity across ADP doses; and hazard ratio, 1.16 [95% confidence interval, 1.02–1.33] [ P =0.029] for highest quartile of ADP response at 1.0 μmol/L versus others). No association was observed for collagen lag time or any epinephrine measures with incident myocardial infarction or stroke. Conclusions: Intrinsic hyperreactivity to low‐dose ADP in our community‐based sample, who were free of CVD and any antiplatelet therapy, is associated with future arterial thrombosis during a 20‐year follow‐up. These findings reinforce ADP activation inhibition as a critical treatment paradigm and encourage further study of ADP inhibitor‐refractive populations.